Vliv angličtiny na ostatní jazyky, zvláště na češtinu - Bondareva, Anastasiia (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2019)
V mé semestrální práce jsem popsala historii anglického jazyka k porozumění proč tento jazyk je široce používán v dnešní době v jiných zemích. Hlavními důvody půjčování anglických slov jsou kolonizace různých míst ve světě britskou říší a vedení USA v oblasti počítačových technologií, inženýrství a televize. Vysvětluji také jak jsou tyto tendence přijímány ve světě. Negativní a pozitivní aspekty jsou podrobně popsány.

In my semestral thesis a history of the English language was described to understand why this language is widely used nowadays in other countries. The main reasons of borrowing English words are colonization of different places in the world by British Empire and the leadership of USA in the field of computer technologies, engineering and TV. I also explained how these tendencies are excepted in the world. The negative and positive aspects are described in detail.
The Influence of English on Other Languages, Especially Czech
Keywords: Anglický jazyk; přejatá slova; vliv angličtiny; český jazyk; antagonismus.; English language; borrowed words; influence of English language; Czech language; antagonism.